2005
DOI: 10.1038/nature03443
|View full text |Cite|
|
Sign up to set email alerts
|

Specific killing of BRCA2-deficient tumours with inhibitors of poly(ADP-ribose) polymerase

Abstract: Poly(ADP-ribose) polymerase (PARP1) facilitates DNA repair by binding to DNA breaks and attracting DNA repair proteins to the site of damage. Nevertheless, PARP1-/- mice are viable, fertile and do not develop early onset tumours. Here, we show that PARP inhibitors trigger gamma-H2AX and RAD51 foci formation. We propose that, in the absence of PARP1, spontaneous single-strand breaks collapse replication forks and trigger homologous recombination for repair. Furthermore, we show that BRCA2-deficient cells, as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
2,932
3
23

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 4,416 publications
(3,002 citation statements)
references
References 26 publications
44
2,932
3
23
Order By: Relevance
“…The PARP1 inhibition disables such complementary repair mechanisms and renders cells particularly dependent on homologous recombination and therefore on BRCA1/2 function. Consequently, high sensitivity to PARP1 inhibitors is observed in BRCA1/2-deficient tumours (Bryant et al, 2005;Farmer et al, 2005), and enhanced sensitivity is also found in cells with impaired double-strand breaks signalling (McCabe et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The PARP1 inhibition disables such complementary repair mechanisms and renders cells particularly dependent on homologous recombination and therefore on BRCA1/2 function. Consequently, high sensitivity to PARP1 inhibitors is observed in BRCA1/2-deficient tumours (Bryant et al, 2005;Farmer et al, 2005), and enhanced sensitivity is also found in cells with impaired double-strand breaks signalling (McCabe et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…This radiosensitization may result from PARP-mediated Targeting DDR pathways to improve cancer treatment F Al-Ejeh et al inhibition of single-strand break repair at stalled replication forks leading to the creation of DSBs (Haince et al, 2005). Consequently, up to 1000-fold higher sensitivity of BRCA-deficient (Bryant et al, 2005;Farmer et al, 2005;McCabe et al, 2005McCabe et al, , 2006Evers et al, 2008) or FA protein-deficient cells to PARP inhibition seems to depend on the excess of DSBs generated in the presence of compromised HR. Increased G2/M arrest upon PARP inhibition could explain the higher growth inhibition in FA proteindeficient cells .…”
Section: Arrest/senescencementioning
confidence: 99%
“…Increased G2/M arrest upon PARP inhibition could explain the higher growth inhibition in FA proteindeficient cells . It is worth noting that in studies of PARPi in cells harboring defects in DNA repair, the use of the generic term 'cell death' (Bryant et al, 2005;Farmer et al, 2005;Gallmeier and Kern, 2005;McCabe et al, 2005) to describe loss of clonogenicity does not adequately describe the multiple outcomes of DNA damage, which include temporary cell cycle arrest, permanent cell cycle arrest (senescence), autophagy, mitotic catastrophe, apoptosis or necrosis. Some of these outcomes may be reversible, or abrupt, or gradually evolve toward tumor cell death.…”
Section: Arrest/senescencementioning
confidence: 99%
“…A promising novel therapy for OC patients is based on the inhibition of poly(ADP‐ribose) polymerase (PARP), which is synthetically lethal in cancer cells with acquired inactivation of the homologous recombination‐mediated repair pathway [Bryant et al., 2005; Farmer et al., 2005]. Multiple clinical trials with PARP inhibitors, including olaparib and niraparib, have demonstrated tolerability and efficacy of these treatments in OC patients [Audeh et al., 2010; Sandhu et al., 2013].…”
Section: Introductionmentioning
confidence: 99%